2020
DOI: 10.3389/fimmu.2020.00917
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inhibitor Therapy for Myasthenia Gravis

Abstract: Complement activation as a driver of pathology in myasthenia gravis (MG) has been appreciated for decades. The terminal complement component [membrane attack complex (MAC)] is found at the neuromuscular junctions of patients with MG. Animals with experimental autoimmune MG are dependent predominantly on an active complement system to develop weakness. Mice deficient in intrinsic complement regulatory proteins demonstrate a significant increase in the destruction of the neuromuscular junction. As subtypes of MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 59 publications
0
35
0
2
Order By: Relevance
“…It is a synthetic, macrocyclic peptide inhibitor for subcutaneous self-administration with principally the same function as eculizumab, blocking the cleavage of C5 (Beecher et al, 2019;Albazli et al, 2020;Howard et al, 2020). A phase 2 randomized, double blind, placebo-controlled, multicenter clinical trial demonstrated that Zilucoplan administration yielded rapid, meaningful, and sustained improvements over 12 weeks in a broad population of patients with moderate-to-severe acetylcholine-receptor-antibody-positive generalized myasthenia gravis (Howard et al, 2020). A phase 3 trial (Recovery After an Initial Schizophrenia Episode study) investigating the safety, tolerability, and efficacy of Zilucoplan in subjects with generalized myasthenia gravis (https://clinicaltrials.gov/ct2/show/NCT04115293) is currently ongoing.…”
Section: B the Complement System Approach In The Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a synthetic, macrocyclic peptide inhibitor for subcutaneous self-administration with principally the same function as eculizumab, blocking the cleavage of C5 (Beecher et al, 2019;Albazli et al, 2020;Howard et al, 2020). A phase 2 randomized, double blind, placebo-controlled, multicenter clinical trial demonstrated that Zilucoplan administration yielded rapid, meaningful, and sustained improvements over 12 weeks in a broad population of patients with moderate-to-severe acetylcholine-receptor-antibody-positive generalized myasthenia gravis (Howard et al, 2020). A phase 3 trial (Recovery After an Initial Schizophrenia Episode study) investigating the safety, tolerability, and efficacy of Zilucoplan in subjects with generalized myasthenia gravis (https://clinicaltrials.gov/ct2/show/NCT04115293) is currently ongoing.…”
Section: B the Complement System Approach In The Clinicmentioning
confidence: 99%
“…Zilucoplan is an entirely different drug structurally from the antibody mentioned above but with the same principal function. It is a synthetic, macrocyclic peptide inhibitor for subcutaneous self-administration with principally the same function as eculizumab, blocking the cleavage of C5 ( Beecher et al, 2019 ; Albazli et al, 2020 ; Howard et al, 2020 ). A phase 2 randomized, double blind, placebo-controlled, multicenter clinical trial demonstrated that Zilucoplan administration yielded rapid, meaningful, and sustained improvements over 12 weeks in a broad population of patients with moderate-to-severe acetylcholine-receptor-antibody–positive generalized myasthenia gravis ( Howard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that complement cascade has an important role in MG pathogenesis linked to IgG1 antibodies (Abs) against AChR, the benefit of complement inhibitors in MG treatment has been proved [12]. Eculizumab is a humanized recombinant monoclonal antibody that, binding to C5 fragment, prevents its cleavage, formation of complement terminal complex [membrane attack complex (MAC)], and subsequent NMJ damage [13].…”
Section: Complement Inhibitorsmentioning
confidence: 99%
“…Blockade of C5 with mAb has been shown to block inflammatory responses in rheumatoid arthritis ( 56 , 57 ). The use of mAb to C5 has also been approved in patients with paroxysmal nocturnal hemoglobinuria ( 58 ) as well as patients with myasthenia gravis ( 59 ). Using KO mice, the absence of C5aR1 has been shown to block many of the harmful outcomes in septic mice ( 23 , 51 ).…”
Section: Phases Of Polymicrobial Sepsismentioning
confidence: 99%